Life Cycle Assessment and Emission Mass Balance of Cassava-Based Bioethanol: A Feasibility Analysis of Environmental Impacts from Upstream to Downstream in Indonesia - Nur Ayu Fatimah; Alliqa Zafira Hakeki; Lilis Sucahyo (TEKNIK, 2025)
Bioethanol is a promising alternative biofuel for reducing gasoline consumption. Indonesia's bioethanol industry is expanding to achieve the energy mix target through Pertamax Green 95. The government also focuses on energy transition and environmental concerns, especially in the transportation sector. This research aims to inventory and assess the impacts of bioethanol production from cassava in Indonesia and analyze the feasibility of bioethanol consumption in vehicle exhaust emissions. The research method utilizes Life Cycle Assessment (LCA) and emission mass balance as the essential analytical tools. The LCA analysis refers to SNI ISO 14040:2016 and SNI ISO 14044:2017, with a cradle-to-gate scope using ReCiPe 2016 Midpoint (H) to assess the potential environmental impact of Global Warming Potential (GWP), Stratospheric Ozone Depletion (SOD) and Terrestrial Acidification (TAC). Whereas vehicle emission feasibility is analyzed using the emission mass balance method to calculate emission concentrations. The research result shows the environmental impacts per liter of bioethanol production from cassava were GWP 11.88 kg CO2 eq, SOD 5.9x10-6 kg CFC11 eq, and TAC 0.04 kg SO2 eq. Emission feasibility analysis signifies that bioethanol combustion vehicles are lower than conventional gasoline. Therefore, it indicates energy and environmental added value through its life cycle.